Renewable Energy Technology, Economics and Environment - Kaltschmitt, Martin.; Kaltschmitt, Martin.; Streicher, Wolfgang.; Streicher, Wolfgang.; Wiese, Andreas.; Wiese, Andreas. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
This book presents the physical and technical principles of promising ways of utilising renewable energies. In this context, firstly the main characteristics of the available renewable energy streams are outlined. Subsequently, the book presents the technologies of heat provision from passive and active solar systems, ambient air, shallow geothermal energy as well as energy from deep geothermal sources. In the preceding chapters the book addresses the processes of electricity generation from solar radiation (photovoltaic and solar thermal power plant technologies), wind energy, and hydropower. In addition, a brief discussions of harnessing ocean energies is included. The authors provide the important data and parameter sets for the major possibilities of renewable energies utilization which allow an economic and environmental assessment. Such an assessment enables us to judge the chances and limits of the multiple options utilising renewable energy sources.